Results of Biceps Tenotomy in The Treatment of Shoulder Impingement and Rotator Cuff Tears - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2015)
Objective: Outcomes of biceps tenotomy with surgical treatment of rotator cuff tears and subacromial impingement was evaluated. Materials and Methods: Twenty-three shoulders were evaluated. Average age was 55.1 and patients were followed up meanly for 32.6 months. Patients were randomized into 4 groups according to their diagnosis and surgical treatment. Group 1 had 5 shoulders subacromial decompression performed alone, group 2 had 7 shoulders with additional biceps tenotomy. Group 3 had 5 shoulders subacromial decompression and rotator cuff repair performed, group 4 had 6 shoulders with additional biceps tonotomy. Group 2 was compared with group 1 as a control group and group 4 with group 3. Groups were compared according to their own preoperative and postoperative Constant and UCLA rating scales. The level of significance was set at p<0.05. Results: Except group 3, postoperative significant increase in scores was detected in all groups. Conclusion: As a result, arthroscopic tenotomy of long head of biceps tendon is easy and quick, with less need of post operative rehabilitation compared to tenodesis.
Keywords: Rotator cuff; tenotomy; shoulder impingement syndrome; LONG HEAD; ARTHROSCOPIC TENOTOMY; PROXIMAL BICEPS; TENDON; BRACHII; TENODESIS; PATHOLOGY; HUMERUS